Genetic variability of five Periplaneta americana L. (Dyctioptera: Blattidae) populations in southwestern Colombia using the AFLP molecular marker technique. (2023)
The genetic structure of five Periplaneta americana (L.) populations from three cities (Cali, Popayán and Buenaventura) located in southwestern Colombia was estimated using the AFLP molecular marker technique. A set of 174 loci were analyzed, 120 of which were polymorphic. Genetic diversity was estimated at different geographic levels for the total population and between cities. Genetic diversity averaged 0.32. The largest gene flow was detected between two population from Cali (F ST=0.088; Nm=2.6) and the lowest from the third population in this city (Univalle) and Popayán and Buenaventura (F ST=0.13; Nm=1.6 and F ST=0.12; Nm=1.8, respectively). The individuals' low mobility, the population' geographic separation, and possibly genetic drift have resulted in the population of this cockroach species having a significant degree of structuring, both between cities (Phist=0.13; P<0.001) and within them (Phist=0.87; P<0.001). These results suggest a high degree of subdivision within the P. americana population studied.